Analysis of Transformational Leadership and Organizational Communication on Employee Performance Employees with Organizational Commitment as a Mediating Variable in Medan Sunggal District Office - Surya Budi; Muhammad Isa Indrawan; Elfitra Desy Surya (Universitas Dehasen Bengkulu, 2026)
Employee performance is an important factor in determining the quality of public services, especially in sub-district level government agencies. This study aims to analyze the effect of transformational leadership and organizational communication on employee performance with organizational commitment as a mediating variable at the Medan Sunggal Sub-District Office. This study uses a quantitative approach with a census method of all 90 civil servants. Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method with the help of the SmartPLS application. The results showed that transformational leadership had a positive but insignificant effect on employee performance. However, transformational leadership had a positive and significant effect on organizational commitment. Organizational communication was found to have a positive and significant effect on employee performance and organizational commitment. Furthermore, organizational commitment has a positive and significant effect on employee performance. Indirect effect testing shows that organizational commitment is able to significantly mediate the effect of transformational leadership and organizational communication on employee performance. These findings indicate that improving employee performance at the Medan Sunggal Sub-District Office is more effectively achieved by strengthening organizational commitment built by transformational leadership and effective organizational communication. This study is expected to contribute theoretically to the development of public management studies and serve as practical consideration for leaders in improving employee performance through improvements in leadership, communication, and organizational commitment.